Positive reappraisal of stressful situations by children of younger school age - Cywińska, Małgorzata (Kultura-Społeczeństwo-Edukacja, 2018)
Stress as an individual phenomenon is a specific kind of emotional experience usually associated with negative emotions and analysed in their context. However, under certain circumstances stress may also trigger positive emotions; analysing a stressful situation and reflecting upon it may lead one to perceive benefits of stressful experience and undertake positive reappraisal of encountered difficulties. The author’s own empirical research reveals that a considerable percentage of children finishing their early-stage school education believe that it is possible to find something advantageous, good and positive in stressful situations full of negative emotions. Examples of such positive aspects of stress given by those children indicate that for some of them the developmental process that involves coping with difficult situations has already started. The children begin to act independently (analyse the difficult situation, talk about it, ask questions, check the effectiveness of strategies) in order to overcome difficulties and find their meaning in human existence.